THE EFFECT OF ENTREPRENEURIAL ORIENTATION AND MARKET ORIENTATION ON JAKARTA’S CULINARY BUSINESS PERFORMANCE - Fransisca, Thalia; Soelaiman, Lydiawati (International Journal of Application on Economics and Business, 2023)
Entrepreneurial and market orientation have an essential role in encouraging increased business performance. Entrepreneurial orientation is the business's strategic orientation to perform and decide to strengthen its competitive position. Market orientation is a strategy and approach to respond to the market to meet customer needs. The purpose of this study was to determine the effect of entrepreneurial orientation. Entrepreneurial orientation consists of 5 dimensions: risk-taking, innovativeness, proactiveness, competitive aggressiveness, and autonomy, and the effect of market orientation on the performance of culinary businesses in Jakarta. This study used a sample of 100 culinary business owners in Jakarta who were selected by purposive sampling. The PLS-SEM method is used to analyze data in this study. According to study's research results, entrepreneurial and market orientation have a positive impact on the performance of Jakarta's culinary businesses.